State-level changes in health insurance coverage and parental substance use-associated foster care entry. (July 2022) - Stritzel, Haley
Abstract: For many families whose children are placed in foster care, initial contact with the child welfare system occurs due to interactions with the healthcare system, particularly in the context of the opioid epidemic and increased attention to prenatal drug exposure. In the last decade, many previously uninsured families have gained Medicaid health coverage, which has implications for their access to healthcare services and visibility to mandatory reporters. Using administrative foster care case data from the Adoption and Foster Care Analysis and Reporting System Foster Care Files and health insurance data from the American Community Survey, this study analyzes the associations between state-level health insurance coverage and rates of foster care entry due to parental substance use between 2009 and 2019. State-level fixed effects models revealed that public, but not private, health insurance rates were positively associated with rates of foster care entry due to parental substance use. These results support the hypothesis that health insurance coverage may promote greater contact with mandatory reporters among low-income parents with substance use disorders. Furthermore, this study illustrates how healthcare policy may have unintended consequences for the child welfare system. Highlights: Health insurance rates were positively associated with substance use-associated foster care entry. This association was limited to public, but not private, health insurance rates. Health insurance coverage may increase contact with mandatory reporters. Low-income families with substance use disorders need better access to treatment.